Pembatasan Sosial Berskala Besar (PSSB) saat Pandemi Covid-19 dan Dampaknya bagi Pasar Modal Indonesia - Ll. Irman Suhaedading (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2020)
The research aims to see impact of Jakarta’s Large Scale Social Distancing (PSBB) when the Covid-19 pandemic for capital market in Indonesia. The data used are Indonesia Composite Index (IHSG), a month before PSBB (2 March 2020 – 9 April 2020) and during PSBB (13 April 2020 – 5 June 2020). The research used Paired Sample T-Test, for comparing two samples data whether they are related or not.The result: There is no significant different between stock price before PSBB and during PSBB. This point can be explained that investors have been anticipating the impact from Covid-19 pandemic. Likewise, Governor of Bank Indonesia said that PSSB in Jakarta will bring positive impact for money market, so that it makes positive sentiment for investors. Consequently, there is no significant impact for composite stock price